Analysis on cracked commuter aircraft wing under dynamic cruise load by means of XFEM - Wirawan, Nanda; Abdullah, Nur Azam; Akbar, Mahesa; Curiel-Sosa, J.L. (IOP Publishing Ltd, 2018)
In this paper, a new investigation of crack propagation on a commuter aircraft wing is discussed. The aircraft is a 19-seater multi-purpose commuter aircraft designed for a mission on the remote area. The dynamic load acting on the wing is assumed as harmonic load considering aerodynamic lift at a particular excitation frequency. A 3D wingbox CAD model is developed for the numerical simulation. Extended finite element (XFEM) is applied to analyse the crack propagation on the aircraft wing. The crack growth simulation is successfully done, and the results are shown in some details. These results provided a novel insight on the computational simulation of cracked wing structure under dynamic flight load.